Processing of granite quarry solid waste into industrial high silica materials using leaching process with HCl concentration variation - Hendronursito, Yusup; Amin, Muhammad; Sumardi, Slamet; Marjunus, Roniyus; Clarasati, Frista; Birawidha, David Candra; Muttaqqi, Muhammad Al; Isnugroho, Kusno (Jurnal Riset Teknologi Pencegahan Pencemaran Industri, 2020)
This study was aimed to increase granite's silica content using the leaching process with HCl concentration variation. The granite used in this study came from Lematang, South Lampung. This study aims to determine the effect of variations in HCl concentration, particle size, and rotational speed on the crystalline phase and chemical elements formed in the silica product produced from granite. The HCl concentration variations were 6.0 M, 7.2 M, 8.4 M, and 9.6 M, the variation in particle size used was 270 and 400 mesh. Variations in rotational speed during leaching were 500 and 750 rpm. Granite powder was calcined at 1000 ºC for 2 hours. Characterization was performed using X-Ray Fluorescence (XRF), X-Ray Diffraction (XRD), and Inductively Coupled Plasma-Optical Emission Spectroscopy (ICP- OES). The results showed that the silica content increased with increasing HCl concentration, the finer the particle size, and the higher the rotational speed. XRF analysis showed that the silica with the highest purity was leached with 9.6 HCl with a particle size of 400 mesh and a rotational speed of of 750 rpm, which was 73.49%. Based on the results above, by leaching using HCl, the Si content can increase from before. The XRD diffractogram showed that the granite powder formed the Quartz phase.